HUBUNGAN ANTARA KECERDASAN INTRAPERSONAL DENGAN KOMPETENSI KEPRIBADIAN GURU TK DI KECAMATAN TAMPAN KOTA PEKANBARU - Dian Ayu Novitasari; Wusono Indarto; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The aim of this research is to know whether there is correlation between intrapersonal intelligence and personal competence of kindergarten’s teachers at Tampan District of Pekanbaru City. The population of this research is kindergarten’ s teachers at Tampan District of Pekanbaru City that consists of 127 teachers, the samples of this research are 56 teachers which taken by using Slovin formula. Method of this research is Pearson Product Moment correlation to know the correlation between Intrapersonal Intelligence and Personal Competence. The technique of collecting data used questioner in Likert scale form. The technique of analyzing data used scale test and statistic analytical by using SPSS program for Windows Ver. 17. Based of hypothesis there is any significant positive correlation between intrapersonal intelligence and personal competence of kindergarten’s teachers at Tampan District of Pekanbaru City. It could be seen from the result of correlation coefficient that 0,304 and significant level is 0,023<0,05. The level of correlation between intrapersonal intelligence and personal competence of kindergarten’s teachers is in the low category with the rank of determinant coefficient in the amount of KD = r² x 100% = 9,24%, it means that intrapersonal intelligence affect personal competence as much as 9,24%. Key Words: Intrapersonal Intelligence, Personal Competence